ANALISIS BIAYA PADA PROYEK URUGAN LIMESTONE RESTORASI DI BIBIR PANTAI NEW GRASS ROOT REFINERY KILANG MINYAK TUBAN - Sugiyanto; Joni Setiyono (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
In the implementation of construction projects, cost control is one of the most important targets in achieving cost performance status. This study aim to of analyze the cost of the restoration limestone backfill project on the shoreline of the new grass root refinery of the Tuban oil refinery. The data used were obtained from PT. Wira Karya Tehnika as the project contractor who has a budget of IDR 1,596,270,000.00 and a duration of 90 days whereby a planned implementation schedule is from November 19, 2021 to February 16, 2022. The earned value method is used in analyzing data which consists of variables, indicators and index earned value. The results of the analysis obtain a pattern formed on the 3 earned value variables at an integrated curve in the duration of the 1st to 13th week of the project, achieving cost performance status on budget. Furthermore, the analysis results of the cost variance provide very strong certainty that the cost performance of the analyzed project implementation can be controlled very well. Finally, the results of the analysis of the cost performance index is an undeniable fact that the project costs can be controlled very well.